A rapid evaluation method for the copper ore-forming potential of granite

Through the study of the mineral phase characteristics of zircon and apatite in granite and the analysis of volatile content of apatite, combined with the evaluation of magma fluid exfoliation and oxygen elimination, a comprehensive evaluation index of granite mineralization potential was constructed, which solved the problems of long periods, high costs and low accuracy of traditional evaluation methods, and achieved rapid and accurate mineralization potential evaluation.

CN115993663BActive Publication Date: 2025-04-11CHINA UNIV OF GEOSCIENCES (BEIJING)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310034657.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-10
Publication Date
2025-04-11
Estimated Expiration
2043-01-10

AI Technical Summary

Technical Problem

The traditional porphyry copper ore resource potential evaluation methods have problems such as long exploration and evaluation cycle, high cost, low accuracy and poor universality, and it is difficult to effectively evaluate the correlation between granite mass and mineralization.

Method used

By sorting and studying the mineral phase characteristics of zircon and apatite minerals in granite, combining the volatile content of apatite inclusions and monominers, the magma fluid effluent and oxygen elude were evaluated to construct a comprehensive evaluation index of granite mineralization potential.

Benefits of technology

The rapid and accurate evaluation of the potential of copper-forming granite can be achieved, shortened the regional mineralization census and exploration cycle, reduced costs, and improved the accuracy and universality of evaluation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115993663B_ABST
    Figure CN115993663B_ABST
Patent Text Reader

Abstract

The embodiment of the present invention discloses a method for rapid evaluation of the copper mineralization potential of granite. The method comprises: conducting a study on the mineral separation of zircon and apatite minerals in granite and the mineral phase characteristics; conducting a study on the mineral phase characteristics of apatite inclusions of silicate minerals in granite, and zircon chronology and trace element composition analysis; combining the results of the mineral phase characteristic study, conducting a study on the volatile content of apatite inclusions and apatite single minerals, and analyzing the major element composition of amphibole; combining the results of the volatile content study, evaluating whether the granite magmatic fluid has exsolution; combining the results of the major element composition analysis of amphibole, evaluating the oxygen fugacity of the granite magma; evaluating the S content before and after the exsolution of the granite magmatic fluid; and constructing a comprehensive evaluation index for the mineralization potential of granite. The present invention can quickly, accurately, simply and economically evaluate the mineralization of granite, shortening the regional mineralization survey and exploration cycle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiment of the present invention relates to the technical field of solid mineral exploration, and in particular to a method for quickly evaluating the copper mineralization potential of granite. Background Art

[0002] Porphyry copper deposits are the main source of copper production in the world, supplying about 75% of the world's copper. Their formation is usually closely related to calc-alkaline granite. However, not all granites can form minerals, which depends on the properties of the granite magma itself, the exsolution of magmatic fluids and the subsequent hydrothermal evolution process. Traditional regional porphyry copper resource potential evaluation methods mainly include regional geological surveys, whole-rock geochemical analysis, geophysical detection and remote sensing prospecting. They have the disadvantages of long exploration and evaluation cycle, high cost, low accuracy and poor universality, which restrict the further development of regional porphyry copper mineralization survey and evaluation.

[0003] The mineralization magma of large-scale porphyry copper deposits usually has high oxygen fugacity and volatile contents such as water, sulfur, and chlorine. Therefore, it is particularly important to find out the oxidation state, water content, and volatile characteristics of the magma corresponding to the granite body to determine the correlation between the granite body and mineralization in the area. In recent years, some whole-rock geochemical indicators (such as TFe2O3 / FeO, Sr / Y, V / Sc, Eu / Eu*) have been used to reflect the water content and oxidation state characteristics of the melt, and then used as indicators to evaluate the mineralization potential of the porphyry system. However, porphyry systems are usually accompanied by superimposed large-scale hydrothermal alteration activities, which makes the interpretation of whole-rock geochemical data somewhat misleading.

[0004] Studies have shown that minerals in granite (such as amphibole, zircon and apatite) can record the composition information of melts during magma evolution. As a characteristic mineral of water-rich granitic magma, amphibole is closely related to melt composition, temperature, pressure and oxygen fugacity, and is widely used to constrain the state of melts. Zircon and apatite are the most widely developed accessory minerals in granite and can accommodate many variable valence elements (such as Eu, Ce) and volatile elements (such as F, Cl, S). Therefore, their compositions are also widely used to reveal the characteristics and evolution history of granite melts related to porphyry systems. However, apatite micro-phenocrysts in the matrix may be subjected to re-equilibrium with residual melts or transformation by hydrothermal fluids, and F-Cl-OH exhibits a fast diffusion rate in apatite. Therefore, apatite micro-phenocrysts in the matrix will inevitably undergo F-Cl-OH re-equilibrium, and their composition may not reflect the volatile information of the melt during apatite crystallization. However, if apatite crystals are captured and completely wrapped by magmatic minerals of the same period, they can avoid the F-Cl-OH re-equilibrium process and the later hydrothermal transformation, thus recording the real melt information. In addition, apatite can be formed at various stages of magmatic evolution, and the composition of apatite is also closely related to the water saturation state of the melt. This is because many fluid-loving elements (such as Cl, S, LREE, etc.) will be strongly depleted in the melt as the fluid dissolves. Apatite crystallized after fluid dissolution usually has a low Cl content. Therefore, only apatite crystallized in the melt where the fluid is not saturated in the early stage of magmatic evolution can effectively indicate the more primitive magmatic melt information. Although the application of zircon and apatite mineral composition to the evaluation of the mineralization potential of granite is increasing, it is still in the initial exploration stage and there are many problems, which restrict the further development of regional mineralization survey and evaluation. Therefore, the industry urgently needs to develop a systematic and complete method for evaluating the copper mineralization potential of granite based on mineral composition. Summary of the invention

[0005] To this end, an embodiment of the present invention provides a method for rapid evaluation of the copper mineralization potential of granite based on multiple mineral components. The method can rapidly, accurately, simply and economically evaluate the mineralization of granite, thereby shortening the regional mineralization survey and exploration cycle.

[0006] In order to achieve the above purpose, the embodiment of the present invention provides the following technical solutions:

[0007] A method for quickly evaluating the copper mineralization potential of granite, the method comprising:

[0008] Conducting research on the separation of zircon and apatite minerals and their mineral phase characteristics in granite;

[0009] Conduct mineralogy research on apatite inclusions in silicate minerals in granite, as well as zircon geochronology and trace element composition analysis;

[0010] Combined with the results of the study on the mineral phase characteristics of apatite inclusions in silicate minerals in granite, the volatile content of apatite inclusions and apatite single minerals was studied, as well as the major element composition analysis of amphibole;

[0011] Combined with the results of volatile content research, an evaluation is conducted on whether the granitic magmatic fluid has undergone exsolution;

[0012] Combined with the analysis results of major element composition of amphibole, the oxygen fugacity of granitic magma was evaluated.

[0013] To evaluate the S content of granite magmatic fluid before and after exsolution;

[0014] Construct comprehensive evaluation indicators for granite mineralization potential.

[0015] Furthermore, the separation of zircon and apatite minerals in granite and the study of their mineral phase characteristics are carried out, including:

[0016] Select zircon and apatite single minerals from multiple granite sample fragments and make targets;

[0017] The mineral phase characteristics of zircon and apatite were observed using transflection microscopy, backscattered electron imaging, and cathodoluminescence, and the development and characteristics of apatite inclusions in zircon were analyzed;

[0018] The zircon type is determined by comparing it with typical zircon cathodoluminescence images, and the undecretalized magmatic zircons are selected.

[0019] Furthermore, the mineral phase characteristics of apatite inclusions in silicate minerals in granite are studied, including:

[0020] Select several fresh granite samples and slice them to make probe slices;

[0021] Transmission and reflection microscopy, backscattered electron imaging, and cathode luminescence were used to observe the mineral phase characteristics of silicate minerals and the development and characteristics of apatite inclusions, wherein the silicate minerals include amphibole, feldspar, and quartz.

[0022] Furthermore, zircon chronology and trace element composition analysis were conducted, including:

[0023] A certain number of magmatic zircons containing apatite inclusions and without mineral inclusions were selected from the selected undecrystallized magmatic zircons, and zircon geochronology and trace element composition analysis were carried out to exclude the existence of inherited zircons and interference from tiny mineral inclusions rich in light rare earths;

[0024] By comparing the composition characteristics of zircons containing apatite inclusions and clean zircons without mineral inclusions, the trace element content of zircons with little influence was selected to analyze the oxygen fugacity characteristics of magma.

[0025] Furthermore, the volatile content of apatite inclusions and apatite single minerals is studied, including:

[0026] The volatile content of apatite inclusions in the selected apatite single mineral and silicate minerals was studied. First, the samples needed to be polished and the major element composition analysis of the appropriate apatite particles was prioritized. The selection principles were: ① Apatite should be transparent and have a relatively clean surface, basically containing no mineral / fluid inclusions; ② Apatite inclusions should be completely enclosed in the host mineral and away from cracks; ③ Apatite with euhedral-semihedral columnar crystals should be selected; ④ Multiple apatite inclusions in different ring zones should be selected in the same zircon;

[0027] The stoichiometric value of apatite was calculated based on the obtained major element composition of apatite.

[0028] Furthermore, the major element composition analysis of amphibole was carried out, specifically including:

[0029] The major element composition of the selected semi-automorphic-automorphic hornblende that has not been altered was analyzed and the stoichiometric number of hornblende was calculated.

[0030] Furthermore, the evaluation of whether the granitic magmatic fluid has exsolution specifically includes:

[0031] According to the composition of apatite single mineral and apatite inclusions in various minerals, the fluid saturation state in the melt during crystallization can be determined. The specific principles for determination are as follows:

[0032] Apatite crystallized in fluid-unsaturated magma F-ap / X Cl-ap Relatively small, and basically unchanged / slightly decreasing trend, X Cl-ap / X OH-ap and X F-ap / X OH-ap The distribution coefficient of F and Cl shows an upward / downward trend, among which X F-ap , X Cl-ap , X OH-ap Respectively represent the molar contents of F, Cl, and OH in apatite;

[0033] Apatite crystallized in fluid-saturated magma F-ap / X Cl-ap The range of variation is large, and X Cl-ap / X OH-ap and X F-ap / X OH-ap All showed that F-ap / X Cl-ap The tendency to increase as it grows;

[0034] According to Apatite X F -X Cl -X OH The evolution characteristics from the core to the edge of apatite in different ring zones of the same zircon in related figures, as well as the evolution trends of apatite single mineral and apatite inclusions in various silicate minerals, are used to comprehensively analyze the nodes where fluid exsolution of melts occurs, and the apatite data are classified into: apatite crystallized in fluid-unsaturated magma (Ap-m); apatite crystallized in fluid-saturated / fluid-exsoluted magma (Ap-f).

[0035] Furthermore, the oxygen fugacity of granitic magma is evaluated, including:

[0036] According to the analysis results of the major element composition of amphibole, T (Amp) 、H2O (Melt) and fO 2(Amp) , to reflect the crystallization temperature, water content and oxygen fugacity of the magma;

[0037] The selected zircon trace data were analyzed and processed, and the T corresponding to each zircon data was calculated. (Zir) 、Eu / Eu* (Zir) 、Ce / Ce* (Zir) and fO 2(Zir) value to reflect the crystallization temperature and oxygen fugacity of the magma.

[0038] Furthermore, the sulfur content of the granite magma fluid before and after exsolution is evaluated, specifically including:

[0039] Combined with the mineralogy characteristics, the melt crystallization temperature and oxygen fugacity determined by zircon and hornblende composition were used to infer the melt temperature T of apatite crystallization. (Ap) and oxygen fugacity fO 2(Ap) , the distribution coefficient of sulfur between apatite and melt is determined as follows:

[0040] D S ap / m =[D S ap / m (T) / 7.4]×D S ap / m (fO2)

[0041] D S ap / m (T) = –0.0036 × T + 11.052 (700 ° C ≤ T ≤ 1100 ° C), where T represents the melt temperature T when apatite crystallizes (Ap) ;

[0042] D S ap / m (fO2)=p1×x 4 +p2×x 3 +p3×x2 +p4×x+p5, where x represents the melt oxygen fugacity ΔFMQ (–1≤x≤3) during apatite crystallization, p1=–0.000008097, p2=0.0005139, p3=0.2189, p4=0.3576, p5=0.1761;

[0043] Based on the determined distribution coefficient of sulfur between apatite and melt, the sulfur content of the melt before and after fluid exsolution is estimated by combining the unsaturated crystallized apatite in the fluid magma (Ap-m) and the crystallized apatite in the fluid saturated magma (Ap-f):

[0044] The sulfur content of the magmatic fluid before exsolution is S melt-m =(SO 3(Ap-m) ×32 / 80) / D S ap / m ;

[0045] The sulfur content of the magmatic fluid after exsolution is S melt-f =(SO 3(Ap-f) ×32 / 80) / D S ap / m .

[0046] Furthermore, a comprehensive evaluation index of granite mineralization potential is constructed, including:

[0047] The zircon U-Pb age of the granite sample is used to represent its diagenesis age, and compared with the porphyry copper mineralization age in the region to evaluate the possibility of mineralization. If the age of the granite sample is consistent with the regional mineralization age, the possibility of mineralization of the rock mass is high.

[0048] Through comprehensive analysis of the magma oxygen fugacity reflected by the composition of amphibole and zircon, if the results of the amphibole and zircon oxygen fugacity meters reflect similar and high oxygen fugacity within the error range, the potential of the rock mass for mineralization is high;

[0049] Through comprehensive evaluation of the sulfur content in the melt before and after fluid exsolution as reflected by apatite, if fluid exsolution occurs in granite, and the higher the sulfur content in apatite and melt before fluid exsolution, the higher the mineralization potential of the rock mass.

[0050] The embodiments of the present invention have the following advantages:

[0051] Compared with traditional methods of evaluating the mineralization potential of porphyry copper, the technical method of the present invention has the advantages of short testing time, low cost, convenience and speed. It can quickly and effectively distinguish between mineralization rock bodies and ore-poor rock bodies in porphyry systems, greatly shortening the prospecting and exploration cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0053] Figure 1 This is a flow chart of a method for rapid evaluation of the copper mineralization potential of granite provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0054] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] Example 1

[0056] like Figure 1 As shown, this embodiment provides a method for rapid evaluation of the copper mineralization potential of granite, comprising the following steps:

[0057] (1) Study on the mineral sorting and mineral phase characteristics of zircon and apatite in granite;

[0058] (2) Study on the mineral phase characteristics of apatite inclusions in minerals such as hornblende, feldspar, and quartz in granite;

[0059] (3) Zircon geochronology and trace element composition analysis;

[0060] (4) Study on the volatile content (F, Cl, S, etc.) of apatite inclusions and apatite single minerals;

[0061] (5) Analysis of major element composition of hornblende;

[0062] (6) Evaluation of whether exsolution of granitic magmatic fluid occurs;

[0063] (7) Evaluation of oxygen fugacity of granitic magma;

[0064] (8) Evaluation of S content in granitic magmatic fluids before and after exsolution;

[0065] (9) Construction of comprehensive evaluation indicators for granite mineralization potential.

[0066] Step (1) comprises:

[0067] Step (1.1) selecting zircon and apatite single minerals from multiple granite sample fragments and making targets;

[0068] Step (1.2) using transflection microscopy, backscattered electron imaging (BSE), and cathode luminescence (CL) to observe the mineral phase characteristics (size, crystal form, degree of euhedral formation, and zoning characteristics) of zircon and apatite, and to analyze the development and characteristics of inclusions such as apatite in zircon;

[0069] Step (1.3) determines the zircon type (magmatic, hydrothermal or metamorphic zircon) by comparing it with typical zircon CL images, and selects the undecrystallized magmatic zircon for the next step.

[0070] Step (2) comprises:

[0071] Step (2.1) selecting a plurality of fresh granite samples for slicing to make probe slices;

[0072] Step (2.2) uses transflection microscopy, backscattered (BSE) electron imaging, and cathodoluminescence (CL) to observe the mineral phase characteristics of various silicate minerals (feldspar, quartz, biotite, amphibole, etc.) and the development and characteristics of apatite inclusions.

[0073] Step (3) includes:

[0074] Step (3.1) selects a certain number of magmatic zircons containing apatite inclusions and without mineral inclusions from the undecrystallized magmatic zircons selected in step (1.3), and uses LA-ICP-MS testing method to carry out U-Pb dating and trace element composition analysis;

[0075] Step (3.2) requires first checking the zircon U-Pb age to exclude the existence of inherited zircon; secondly, screening the obtained zircon trace data to exclude the interference of components such as light rare earth-rich tiny mineral inclusions (such as apatite, titanite, monazite, etc.). It is recommended to use La<1ppm and Ti<50ppm to exclude the influence of other mineral inclusions;

[0076] Step (3.3) compares the composition characteristics of zircons containing apatite inclusions and clean zircons without mineral inclusions, analyzes the variation patterns of zircon Hf content and Th / U, Gd / Yb and other element content ratios, and evaluates whether the crystallization of apatite and other minerals has a significant impact on the zircon composition. Selects zircon trace element content with little impact to analyze the oxygen fugacity characteristics of magma.

[0077] The step (4) comprises:

[0078] Step (4.1) is to carry out major element composition analysis by using electron / ion probe test method on the apatite single mineral selected in step (1.2) and the apatite inclusions in other silicate minerals selected in step (2.2) and step (3.1). First, the sample needs to be polished and the appropriate apatite particles are analyzed first. The optimization principle is as follows: ① the apatite is transparent and has a relatively clean surface, and basically does not contain mineral / fluid inclusions; ② the apatite inclusions need to be completely enclosed in the host mineral and away from the cracks; ③ select apatite with euhedral-semihedral columnar crystals (with a cross-section shape approximately parallel to the c-axis) to reduce the influence of halogen element diffusion and migration during the test and analysis process; ④ multiple apatite inclusions in different ring zones in the same zircon are preferentially selected for analysis;

[0079] In step (4.2), the major element composition of the obtained apatite is checked. The data with fluorine content exceeding the end-member value of fluoroapatite (F>3.77wt%) are not discussed, considering that they reflect experimental test errors or fluid exsolution leading to enrichment of melt F. Then, the apatite stoichiometric number (pfu) is calculated for the screened data to carry out the next step.

[0080] Step (5) is to carry out major element composition analysis on the semi-automorphic-automorphic unaltered amphibole selected in step (2.2) by using electron / ion probe testing method, and calculate the amphibole stoichiometric number (pfu) based on the data obtained to carry out the next step.

[0081] Step (6) comprises:

[0082] Step (6.1) is to X-ray the components of the apatite single mineral and apatite inclusions in various minerals obtained in step (4.2). Cl-ap / X OH-ap vs.X F-ap / X Cl-ap , X Cl-ap / X OH-ap vs.X F-ap / X OH-ap The saturation state of the fluid in the melt during crystallization is determined by combining the trend of the composition of apatite F, Cl and OH in the model published by Stock et al. in the Journal of Petrology in 2018. The specific principles for determination are as follows:

[0083] (a) Apatite crystallized in fluid-unsaturated magma. F-ap / X Cl-ap Relatively small, and basically unchanged / slightly decreasing trend, X Cl-ap / X OH-ap and X F-ap / X OH-apThe distribution coefficient of F and Cl shows an upward / downward trend (X F-ap , X Cl-ap , X OH-ap Respectively represent the molar content of F, Cl, and OH in apatite);

[0084] (b) Apatite crystallized in fluid-saturated magma F-ap / X Cl-ap The range of variation is large, and X Cl-ap / X OH-ap and X F-ap / X OH-ap All showed that F-ap / X Cl-ap The trend of increasing.

[0085] Step (6.2) through step (6.1) apatite X F -X Cl -X OH The evolution characteristics from the core to the edge of apatite in different ring zones of the same zircon in related figures, as well as the evolution trends of apatite single mineral and apatite inclusions in various silicate minerals, are used to comprehensively analyze the nodes where fluid exsolution of melts occurs, and the apatite data are classified into: apatite crystallized in fluid-unsaturated magma (Ap-m); apatite crystallized in fluid-saturated / fluid-exsoluted magma (Ap-f).

[0086] Step (7) comprises:

[0087] Step (7.1) is to measure the hornblende component obtained in step (5) using an existing hornblende thermometer, hygrometer and oxygen fugacity meter. (Amp) 、H2O (Melt) and fO 2(Amp) Calculated to reflect the crystallization temperature, water content, and oxygen fugacity of the magma:

[0088] T (Amp) 、H2O (Melt) and fO 2(Amp) The value can be calculated by referring to the amphibole thermometer, hygrometer and oxygen fugacity meter published by Ridiolfi et al. in the journal Contributions to Mineralogy and Petrology in 2010. The specific formula is as follows:

[0089] T (Amp) (℃)=(–151.487×Si*)+2041

[0090] H2O (Melt) (wt%) = (5.215 × Al*) + 12.28

[0091] fO 2(Amp)(ΔNNO) = (1.644 × Mg*) – 4.01

[0092] Where Si*=Si+(Al IV / 15)–(2×Ti IV )–(Al IV / 2)–(Ti VI / 1.8)+(Fe 3+ / 9)+(Fe 2+ / 3.3)+(Mg / 26)+( B Ca / 26)+( B Na / 1.3)+( A Na / 15)+((1– A Na– A K) / 2.3); Al*=Al VI +(Al IV / 13.9)–((Si+Ti VI ) / 5)–(Fe 2+ / 3)–(Mg / 1.7)+( B Ca+(1– A Na– A K) / 1.2)+( A Na / 2.7)–1.56×K–(Fe# / 1.6); Mg*=Mg+(Si / 47)–(Al IV / 9)–(1.3×Ti VI )–(Fe 3+ / 3.7)–(Fe 2+ / 5.2)–( B Ca / 20)–( A Na / 2.8)+((1– A Na– A K) / 9.5);

[0093] Step (7.2) analyzes and processes the zircon trace data screened out in steps (3.2, 3.3) and calculates the T corresponding to each zircon data. (Zir) 、Eu / Eu* (Zir) 、Ce / Ce* (Zir) and fO 2(Zir) Values ​​to reflect the crystallization temperature and oxygen fugacity of the magma:

[0094] T (Zir) The value is calculated with reference to the zircon titanium thermometer published by Ferry and Watson in the journal Contributions to Mineralogy and Petrology in 2007. The specific formula is as follows:

[0095] T (Zir)(K)=(4800±86) / [(5.711±0.072)–log(Ti-in-zircon)–logαSiO2+

[0096] logαTiO2], where αSiO2 and αTiO2 represent the activity coefficients of SiO2 and TiO2 in the melt, respectively. The value of αSiO2 in granite melt is usually 1, and the value of αTiO2 is usually 0.5 to 1;

[0097] Eu / Eu* (Zir) The value is calculated based on the formula published by Ballard et al. in the journal Contributions to Mineralogy and Petrology in 2002. The specific formula is as follows:

[0098] Eu / Eu* (Zir) =(Eu / 0.087) / [(Sm / 0.231)×(Gd / 0.306)] 1 / 2 ;

[0099] Ce / Ce* (Zir) The value is calculated based on the formula published by Loader et al. in the journal Earth and Planetary Science Letters in 2017. The specific formula is as follows:

[0100] Ce / Ce* (Zir) =(Ce / 0.612) / [(Nd / 0.467) 2 / (Sm / 0.153)];

[0101] fO 2(Zir) The value is calculated with reference to the zircon oxygen fugacity meter formula published by Loucks et al. in the Journal of Petrology in 2020. The specific formula is as follows:

[0102] fO 2(Zir) (ΔFMQ) = 3.998 × log [(Ce / U i )×(U i / Ti) 1 / 2 ]+2.284

[0103] U i =U×exp[age×0.000155125+0.0072×exp(age×0.00098485)].

[0104] Step (8) comprises:

[0105] Step (8.1) Combined with the mineralogy characteristics, the melt crystallization temperature and oxygen fugacity determined by zircon and amphibole components are used to infer the melt temperature (T) during apatite crystallization. (Ap) ) and oxygen fugacity (fO 2(Ap) ), considering the distribution coefficient of sulfur between apatite and melt (D S ap / m ) is mainly controlled by oxygen fugacity and temperature. Combining the experimental research data published by Konecke et al. in Geochimica et Cosmochimica Acta in 2019 and the experimental research data published by Parat and Holtz in Contributions to Mineralogy and Petrology in 2004, the distribution coefficient of sulfur between apatite and melt was established as follows:

[0106] D S ap / m =[D S ap / m (T) / 7.4]×D S ap / m (fO2)

[0107] D S ap / m (T) = –0.0036 × T + 11.052 (700 ° C ≤ T ≤ 1100 ° C), where T represents the melt temperature T when apatite crystallizes (Ap) ;

[0108] D S ap / m (fO2)=p1×x 4 +p2×x 3 +p3×x 2 +p4×x+p5, where x represents the melt oxygen fugacity ΔFMQ (–1≤x≤3) during apatite crystallization, p1=–0.000008097, p2=0.0005139, p3=0.2189, p4=0.3576, p5=0.1761.

[0109] Step (8.2) estimates the sulfur content of the melt before and after fluid exsolution by using the distribution coefficient of sulfur between apatite and melt determined in step (8.1) and the apatite crystallized in the unsaturated fluid magma (Ap-m) and the apatite crystallized in the fluid saturated magma (Ap-f) classified in step (6.2):

[0110] The S content of the magmatic fluid before exsolution is S melt-m =(SO 3(Ap-m) ×32 / 80) / D S ap / m ;

[0111] The S content of the magmatic fluid after dissolution is S melt-f =(SO 3(Ap-f) ×32 / 80) / D S ap / m .

[0112] Step (9) comprises:

[0113] Step (9.1) The zircon U-Pb age of the granite sample obtained through steps (3.2, 3.3) represents its diagenetic age, and is compared with the porphyry copper mineralization age in the region to evaluate the possibility of mineralization. If the age of the granite sample is consistent with the regional mineralization age, the possibility of rock mass mineralization is high;

[0114] Step (9.2) is to conduct a comprehensive analysis of the magma oxygen fugacity reflected by the amphibole and zircon components. If the amphibole and zircon oxygen fugacity meter results reflect similar and high oxygen fugacity within the error range, the rock mass has a high mineralization potential;

[0115] Step (9.3) is to comprehensively evaluate the S content in the melt before and after melt exsolution, as reflected by apatite. If fluid exsolution occurs in granite, and the higher the S content in apatite and melt before fluid exsolution, the higher the mineralization potential of the rock mass.

[0116] The advantages of the present invention are that compared with traditional means of evaluating the mineralization potential of porphyry copper, the technical method of the present invention has the advantages of short testing time, low cost, convenience and speed, and can quickly and effectively distinguish between mineralization rock bodies and ore-poor rock bodies in porphyry systems, greatly shortening the prospecting and exploration period.

[0117] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.

Claims

1. A method for rapid evaluation of the copper mineralization potential of granite, characterized in that: The method comprises: Conducting research on the separation of zircon and apatite minerals and their mineral phase characteristics in granite; Conduct mineralogy research on apatite inclusions in silicate minerals in granite, as well as zircon geochronology and trace element composition analysis; Combined with the results of the study on the mineral phase characteristics of apatite inclusions in silicate minerals in granite, the volatile content of apatite inclusions and apatite single minerals was studied, as well as the major element composition analysis of amphibole; Combined with the results of volatile content research, an evaluation is conducted on whether the granitic magmatic fluid has undergone exsolution; Combined with the analysis results of major element composition of amphibole, the oxygen fugacity of granitic magma was evaluated. To evaluate the S content of granite magmatic fluid before and after exsolution; Construct comprehensive evaluation indicators for granite mineralization potential.

2. The rapid evaluation method for the copper mineralization potential of granite according to claim 1 is characterized in that: Conducting the separation of zircon and apatite minerals in granite and studying their mineral phase characteristics, including: Select zircon and apatite single minerals from multiple granite sample fragments and make targets; The mineral phase characteristics of zircon and apatite were observed using transflection microscopy, backscattered electron imaging, and cathodoluminescence, and the development and characteristics of apatite inclusions in zircon were analyzed; The zircon type is determined by comparing it with typical zircon cathodoluminescence images, and the undecretalized magmatic zircons are selected.

3. The rapid evaluation method for the copper mineralization potential of granite according to claim 1 or 2, characterized in that: The mineral phase characteristics of apatite inclusions in silicate minerals in granite are studied, including: Select several fresh granite samples and slice them to make probe slices; Transmission and reflection microscopy, backscattered electron imaging, and cathode luminescence were used to observe the mineral phase characteristics of silicate minerals and the development and characteristics of apatite inclusions, wherein the silicate minerals include amphibole, feldspar, and quartz.

4. The rapid evaluation method for the copper mineralization potential of granite according to claim 3 is characterized in that: Conduct zircon geochronology and trace element composition analysis, including: A certain number of magmatic zircons containing apatite inclusions and without mineral inclusions were selected from the selected undecrystallized magmatic zircons, and zircon geochronology and trace element composition analysis were carried out to exclude the existence of inherited zircons and interference from tiny mineral inclusions rich in light rare earths; By comparing the composition characteristics of zircons containing apatite inclusions and clean zircons without mineral inclusions, the trace element content of zircons with little influence was selected to analyze the oxygen fugacity characteristics of magma.

5. The rapid evaluation method for the copper mineralization potential of granite according to claim 4 is characterized in that: Conduct research on apatite inclusions and the volatile content of apatite single minerals, including: The volatile content of apatite inclusions in the selected apatite single mineral and silicate minerals was studied. First, the samples needed to be polished and the major element composition analysis of the appropriate apatite particles was prioritized. The selection principles were: ① Apatite should be transparent and have a relatively clean surface, basically containing no mineral / fluid inclusions; ② Apatite inclusions should be completely enclosed in the host mineral and away from cracks; ③ Apatite with euhedral-semihedral columnar crystals should be selected; ④ Multiple apatite inclusions in different ring zones should be selected in the same zircon; The stoichiometric value of apatite was calculated based on the obtained major element composition of apatite.

6. The rapid evaluation method for the copper mineralization potential of granite according to claim 4 is characterized in that: The main element composition analysis of amphibole is carried out, including: The major element composition of the selected semi-automorphic-automorphic hornblende that has not been altered was analyzed and the stoichiometric number of hornblende was calculated.

7. The rapid evaluation method for the copper mineralization potential of granite according to claim 1 is characterized in that: The evaluation of whether the granite magmatic fluid has exsolution specifically includes: According to the composition of apatite single mineral and apatite inclusions in various minerals, the fluid saturation state in the melt during crystallization can be determined. The specific principles for determination are as follows: Apatite crystallized in fluid-unsaturated magma F-ap / X Cl-ap Relatively small, and basically unchanged / slightly decreasing trend, X Cl-ap / X OH-ap and X F-ap / X OH-ap The distribution coefficient of F and Cl shows an upward / downward trend, among which X F-ap , X Cl-ap , X OH-ap Respectively represent the molar contents of F, Cl, and OH in apatite; Apatite crystallized in fluid-saturated magma F-ap / X Cl-ap The range of variation is large, and X Cl-ap / X OH-ap and X F-ap / X OH-ap All showed that F-ap / X Cl-ap The tendency to increase as it grows; According to Apatite X F -X Cl -X OH The evolution characteristics from the core to the edge of apatite in different ring zones of the same zircon in related figures, as well as the evolution trends of apatite single mineral and apatite inclusions in various silicate minerals, are used to comprehensively analyze the nodes where fluid exsolution of melts occurs, and the apatite data are classified into: apatite crystallized in fluid-unsaturated magma (Ap-m); apatite crystallized in fluid-saturated / fluid-exsoluted magma (Ap-f).

8. The method for rapid evaluation of the copper mineralization potential of granite according to claim 1, characterized in that: Conduct oxygen fugacity evaluation of granitic magma, including: According to the analysis results of the major element composition of amphibole, T (Amp) 、H2O (Melt) and fO 2(Amp) , to reflect the crystallization temperature, water content and oxygen fugacity of the magma; The selected zircon trace data were analyzed and processed, and the T corresponding to each zircon data was calculated. (Zir) 、Eu / Eu* (Zir) 、Ce / Ce* (Zir) and fO 2(Zir) value to reflect the crystallization temperature and oxygen fugacity of the magma.

9. The rapid evaluation method for the copper mineralization potential of granite according to claim 1, characterized in that: The sulfur content of granite magma fluid before and after exsolution is evaluated, including: Combined with the mineralogy characteristics, the melt crystallization temperature and oxygen fugacity determined by zircon and hornblende composition were used to infer the melt temperature T of apatite crystallization. (Ap) and oxygen fugacity fO 2(Ap) , the distribution coefficient of sulfur between apatite and melt is determined as follows: D S ap / m =[D S ap / m (T) / 7.4]×D S ap / m (fO2) D S ap / m (T) = –0.0036 × T + 11.052 (700 ° C ≤ T ≤ 1100 ° C), where T represents the melt temperature T when apatite crystallizes (Ap) ; D S ap / m (fO2)=p1×x 4 +p2×x 3 +p3×x 2 +p4×x+p5, where x represents the melt oxygen fugacity ΔFMQ (–1≤x≤3) during apatite crystallization, p1=–0.000008097, p2=0.0005139, p3=0.2189, p4=0.3576, p5=0.1761; Based on the determined distribution coefficient of sulfur between apatite and melt, the sulfur content of the melt before and after fluid exsolution is estimated by combining the unsaturated crystallized apatite in the fluid magma (Ap-m) and the crystallized apatite in the fluid saturated magma (Ap-f): The sulfur content of the magmatic fluid before exsolution is S melt-m =(SO 3(Ap-m) ×32 / 80) / D S ap / m ; The sulfur content of the magmatic fluid after exsolution is S melt-f =(SO 3(Ap-f) ×32 / 80) / D S ap / m .

10. The rapid evaluation method for the copper mineralization potential of granite according to claim 1, characterized in that: The comprehensive evaluation index of granite mineralization potential is constructed, including: The zircon U-Pb age of the granite sample is used to represent its diagenesis age, and compared with the porphyry copper mineralization age in the region to evaluate the possibility of mineralization. If the age of the granite sample is consistent with the regional mineralization age, the possibility of mineralization of the rock mass is high. Through comprehensive analysis of the magma oxygen fugacity reflected by the composition of amphibole and zircon, if the results of the amphibole and zircon oxygen fugacity meters reflect similar and high oxygen fugacity within the error range, the potential of the rock mass for mineralization is high; Through comprehensive evaluation of the sulfur content in the melt before and after fluid exsolution as reflected by apatite, if fluid exsolution occurs in granite magma and the higher the sulfur content in apatite and melt before fluid exsolution, the higher the mineralization potential of the rock mass.

Citation Information

Patent Citations

  • Mineral exploration method for quickly judging mineralization potential of vein-shaped ore deposit by using zircon

    CN111505005A

  • Method and system for determining sulfur content of granite melt

    CN115356462A